PERAN BAHASA DALAM PENGEMBANGAN PESERTA DIDIK DAN PEMBANGUNAN BANGSA - Supriyanti, Nury (Pusat Pengembangan Bahasa, 2016)
Then paper proposes the discussion of the signifcant role of language in developing students and the national development. Language and its role in educating people of a nation are often forgotten because they are often taken for granted. We often undermine the contribution of the language that is used to educate our nation. The language that we use to express important ideas, to deliver moral teachings valued highly by the nation, to shape the young generationâs character obviously brings with it things that the type of the language has. Language in use may not ideologically neutral. The discussion is also about the fact that language is used for learning, that is as a tool for understanding. Language is also a tool for interacting with others from which people learn. Another notion proposed is that language is the main tool in instruction especially in the classroom. In the teaching of language, the target language is used as much is possible in the course of the teaching. All parties involved in the education of the nation understand the position of the languages used in the teaching of the young generation including the foreign languages needed to develop the nation.